2004
DOI: 10.1300/j013v40n02_06
|View full text |Cite
|
Sign up to set email alerts
|

Access to Women's Health Care: A Qualitative Study of Barriers Perceived by Homeless Women

Abstract: Homelessness is an escalating national problem and women are disproportionately affected. Nevertheless, few studies have focused on the special circumstances associated with being a homeless woman. For instance, while both genders experience serious barriers to obtaining health care, homeless women face an additional burden by virtue of their sexual and reproductive health needs. The current study was conducted as the first stage of a qualitative/quantitative investigation of homeless women's access and barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
134
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(138 citation statements)
references
References 8 publications
3
134
1
Order By: Relevance
“…The high prevalence of mental health problems among homeless women suggests that mental health care services are not adequately meeting the needs of homeless women. Many homeless women experience barriers to accessing the health care system (Gelberg, Browner, Lejano, & Arangua, 2004;Lewis, Andersen, & Gelberg, 2003;Lim, Andersen, Leake, Cunningham, & Gelberg, 2002), and among women with children, prioritization of their children's needs, fear of losing custody of their children, and meeting basic family needs may function as additional deterrents for seeking mental health care (Tam, Zlotnick, & Bradley, 2008;Weinreb, Nicholson, Williams, & Anthes, 2007). The use of alternative models of care -for example, the psychiatric outreach model described by Farrell et al (2005), which offers flexible, open-ended outreach services to individuals considered "hard to serve" -may help reduce some of these barriers to accessing care and ensure improved access to mental health care services among this population.…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of mental health problems among homeless women suggests that mental health care services are not adequately meeting the needs of homeless women. Many homeless women experience barriers to accessing the health care system (Gelberg, Browner, Lejano, & Arangua, 2004;Lewis, Andersen, & Gelberg, 2003;Lim, Andersen, Leake, Cunningham, & Gelberg, 2002), and among women with children, prioritization of their children's needs, fear of losing custody of their children, and meeting basic family needs may function as additional deterrents for seeking mental health care (Tam, Zlotnick, & Bradley, 2008;Weinreb, Nicholson, Williams, & Anthes, 2007). The use of alternative models of care -for example, the psychiatric outreach model described by Farrell et al (2005), which offers flexible, open-ended outreach services to individuals considered "hard to serve" -may help reduce some of these barriers to accessing care and ensure improved access to mental health care services among this population.…”
Section: Discussionmentioning
confidence: 99%
“…68 Women suffering from drug abuse, violence, or depression seem to have the greatest unmet health care needs. 69 Homeless women may not view health care as a priority because of competing needs: finding a place to sleep, enough food to eat, a place to wash, or a place to go to the bathroom, 70 or may experience stigmatization from health care workers, 71 resulting in decreased access to health care in general and for HCV infection in particular. While homeless men also experience similar needs, research suggests that impoverished women may prioritize safety and survival over health care.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies using qualitative research design identified several of the same barriers to perinatal health care mentioned by the women in the focus groups, including access and transportation difficulties, a need for material and financial assistance, and a feeling of being stigmatized at doctors' visits. 19,20 Indeed, risk factors are confounded by a relative lack of access to health care recommended for all pregnant women. Homeless women are less likely to attend prenatal and well-child appointments at the recommended intervals.…”
Section: Discussionmentioning
confidence: 99%